Economics of Happiness: A Social Study on Determinants of Well-Being among Employees in a State University - Leomarich F. Casinillo; Emily L. Casinillo; Ma. Rachel Kim L. Aure (Philippine Social Science Journal, 2021)
This study aimed to elucidate the level of happiness and its influencing determinants among employees (teaching and non-teaching) of Visayas State University, Baybay City, Leyte, Philippines. With the aid of purposive sampling, the study engaged 162 employees as participants in the survey to gather richer information. The study utilized primary data, which were collected through a developed and structured questionnaires. The data were analyzed through descriptive analysis and econometric modeling. Results revealed that non-teaching employees are more likely happy working in a university. It was found out that the predictors of happiness in working in a university are: age, years in service, permanent status, opportunities for promotion, and fair administration. Employees found their respective jobs as challenging, enjoyable and rewarding. However, results showed that income is not a determinant of employees' happiness. Furthermore, employees who are socially oriented and physically healthy are more likely happy workers.